Effects of different feeds on the performance of black crickets (Gryllus assimilis) - de Souza, Daniela Fonseca Melo; dos Santos, Lucas Gabryel Maciel; Buzanskas, Marcos Eli [UNESP]; Siqueira, Jeanne Broch; Iared, Fabio; Melo, e Thiago Vasconcelos (Springer Nature, 2025)
This study evaluated the performance of black crickets (Gryllus assimilis) fed three types of commercial feed intended for different species (birds, rabbits and dogs) with crude protein levels varying between 15 and 20%. The experiment was carried out over 60 days at the Laboratory for the Production of Insects for Animal Feeding (LPINA) in a completely randomised design, with three treatments and four replications, totaling 12 batches of 10 crickets each (40 crickets per treatment, totaling 120 crickets). Feed consumption, weight gain, final weight, fecal weight and cricket mortality were analysed. For statistical analysis, the results of the variables studied were subjected to variance analysis, and the means were compared via Tukey’s test at 0.05 probability via the R statistical program. The results indicated that the different protein levels did not significantly influence cricket performance. Mortality was greater in the group fed dog food, possibly due to a greater number of females and consequent cannibalism. Further studies on nutritional requirements and digestibility are needed to optimise the production of Gryllus assimilis.
Keywords: Alternative proteins; Entomology; Insect farming